2012
DOI: 10.1002/jbmr.1571
|View full text |Cite
|
Sign up to set email alerts
|

Tonicity enhancer binding protein (TonEBP) and hypoxia-inducible factor (HIF) coordinate heat shock protein 70 (Hsp70) expression in hypoxic nucleus pulposus cells: Role of Hsp70 in HIF-1α degradation

Abstract: The objective of our study was to examine the regulation of hypoxic expression of Hsp70 in nucleus pulposus cells and to determine if Hsp70 promoted HIF-1α degradation. Rat nucleus pulposus cells were maintained in culture in either 21% or 1% oxygen. To determine the regulation of Hsp70 expression by Tonicity enhancer binding protein (TonEBP) and HIF-1/2, loss- and gain-of-function experiments and mutational analysis of Hsp70 promoter were performed. Hypoxia increased Hsp70 expression in nucleus pulposus cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…Careful work by Risbud and coworkers has shown that NP cells constitutively express HIF-1α and HIF-2α under both normoxia and hypoxia [92, 93]. Consistent with this observation, alternative oxygen-independent means of HIF-α degradation and activity have been shown to impact protein levels in NP cells [94-96]. Taken together, unique regulation of HIF protein turnover and activity in NP cells suggests its importance in NP physiology.…”
Section: Markers Specific To Cell Function In the Np Microenvironmentmentioning
confidence: 77%
“…Careful work by Risbud and coworkers has shown that NP cells constitutively express HIF-1α and HIF-2α under both normoxia and hypoxia [92, 93]. Consistent with this observation, alternative oxygen-independent means of HIF-α degradation and activity have been shown to impact protein levels in NP cells [94-96]. Taken together, unique regulation of HIF protein turnover and activity in NP cells suggests its importance in NP physiology.…”
Section: Markers Specific To Cell Function In the Np Microenvironmentmentioning
confidence: 77%
“…regulation of Hsp70 and GlcAT-I promoters in nucleus pulposus cells (6,11). Related to this discussion, one possibility is that hypoxia may exert its effects on CCN2 through the modulation of Fli1 or Ets-1, members of the Ets family of transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…HIF is a basic helix-loop-helix transcription factor comprising a constitutively expressed ␤ subunit and an ␣ subunit that undergoes degradation by both oxygen-dependent and -independent pathways (5,6). When stabilized, the ␣ subunit dimerizes with the ␤ subunit and binds to hypoxia response elements (HREs) in the promoter of target genes.…”
mentioning
confidence: 99%
“…HSF1 trimerization and activation of its transactivation domain are regulated by multiple serine and threonine phosphorylation events. Transcription of Hsps is also influenced by other transcription factors, including STAT-1, STAT-3, and NF-IL-6 (22)(23)(24), tonicity enhancer-binding protein and hypoxia-inducible factor 1 (25) and NFB (26). We previously showed that HSF1 trimerization and Hsp70 transcription were activated in A549 cells by exposure to mild hyperthermia (38.5°C), that Hsp70 transcription increased as the exposure temperature increased from 38.5°C to 42°C, and that increased transcription was associated with additional HSF1 phosphorylation but not additional HSF1 trimerization (27).…”
mentioning
confidence: 99%